Impact of sarcopenia and sarcopenic obesity on survival in patients with primary liver cancer: a systematic review and meta-analysis - Li, Xuanmei; Huang, Xue; Lei, Lifu; Tong, Shiwen (Frontiers in Nutrition, 2023)
Background: Sarcopenia and sarcopenic obesity are associated with an increased possibility of adverse clinical outcomes; however, the effects of sarcopenia and sarcopenic obesity on patients with primary liver cancer remain controversial. Therefore, the present study aimed to determine the impact of sarcopenia and sarcopenic obesity on survival in patients with primary liver cancer. Methods: We searched studies published in English in PubMed, Embase, Web of Science, and Cochrane library from database up to November 13, 2022. Cohort studies that reported the association between sarcopenia, sarcopenic obesity, and patient survival were included. Results: A total of 64 cohort studies with data on 11,970 patients with primary liver cancer were included in the meta-analysis. Sarcopenia was associated with poor overall survival in patients with primary liver cancer (adjusted hazard ratio [HR]: 2.11, 95% confidence interval [CI]: 1.89–2.36, P < 0.0001), with similar findings for sarcopenic obesity (adjusted HR: 2.87, 95% CI: 2.23–3.70, P < 0.0001). Sarcopenia was also associated with poor overall survival across the subgroups analyzed by ethnicity, type of liver cancer, treatment modalities, method used to define sarcopenia, and etiology of liver cancer. We also found a negative correlation between sarcopenia, sarcopenic obesity, and recurrence-free/disease-free survival (adjusted HR: 1.73, 95% CI: 1.50–1.99, P < 0.001; adjusted HR: 2.28, 95% CI: 1.54–3.35, P < 0.001, respectively). Conclusion: Sarcopenia and sarcopenic obesity were significantly associated with poor overall survival and recurrence-free/disease-free survival in patients with primary liver cancer.